2013
DOI: 10.5267/j.dsl.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A state-of-art review on supplier selection problem

Abstract: Many supplier selection problems are involved with various criteria such as quality of supplier, price, delivery time, etc. This paper presents a survey on the implementation of using different multi criteria decision making (MCDM) methods for supplier selection problems. The reviews covers recent advances of MCDM techniques such as data envelopment analysis (DEA), analytical hierarchy process, etc. over the period 2000-2012. The review also reveals that nearly 60% of the applications are associated with busin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…They also presented the most popular criterion in supplier selection problem. Khodadadzadeh and Sadjadi [7] reviewed the literature between the years 2000 and 2013 where data envelopment analysis (DEA) applications were used in different industries for supplier selection, and presented that 60% is related to business, whereas 4% is related to healthcare. Chai et al [8] conducted a systematic literature review between the years 2008 and 2012 on various applications of decision-making methods for supplier selection.…”
Section: Introductionmentioning
confidence: 99%
“…They also presented the most popular criterion in supplier selection problem. Khodadadzadeh and Sadjadi [7] reviewed the literature between the years 2000 and 2013 where data envelopment analysis (DEA) applications were used in different industries for supplier selection, and presented that 60% is related to business, whereas 4% is related to healthcare. Chai et al [8] conducted a systematic literature review between the years 2008 and 2012 on various applications of decision-making methods for supplier selection.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity analysis also showed that all the criteria were robust. For more research on supplier and site selection for the upstream supply chain, see Koul and Verma (2012), Khodadadzadeh and Sadjadi (2013), Costa et al (2016), Teniwut et al (2019), andAchatbi et al (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Proposed a detailed review of supplier selection and projected the practicability of MCDM techniques for futures researcher and studied the feasibility of these techniques in the current published literature. Khodadadzadeh et al, 2013 MCDM, Data development analysis (DEA), TOPSIS, and AHP Proposed a survey of employing different form of MCDM techniques for supplier selection and evaluation such as DEA, TOPSIS, and AHP. Ghorbani et al, 2013 Fuzzy TOPSIS, and Kano model.…”
Section: Tablementioning
confidence: 99%